ANALYSIS OF MAJOR RISK FACTORS IMPACTING HEALTHY LIFESTYLE PRACTICES - Urazalieva I. R.; Kamilova M. O. (Modern American Journals, 2026)
The findings indicate that assessing behavioral factors is essential for identifying healthy lifestyle practices and disease prevalence among the population. Numerous studies have demonstrated that incorporating dietary interventions into disease management leads to improved health outcomes. Increases in body mass index and declines in physical activity have also led to a rise in unhealthy eating behaviors. Several literature reviews were conducted to assess the effects of interventions targeting the occupational health of healthcare workers. Workplace interventions have been shown to be potentially effective, and strategies using a variety of interventions have demonstrated benefits in combating overeating.
Keywords: Lifestyle-related diseases, sedentary behavior, nutrition interventions, health promotion, occupational health, obesity and overweight, preventive healthcare, health behavior change.